Risk Factors for the Development of Bacteremia in Pediatric Hemato-Oncology Patients in a Public Third Level Hospital - Alejandra Camila Espinoza-Quiroz; Juan Pablo Rodriguez-Auad; Miguela A Caniza (Journal of the Pediatric Infectious Diseases Society, 2026)
Abstract Background The use of intensive chemotherapy has improved childhood cancer survival but increases severe neutropenia and the risk of infections. Several studies have identified factors that predispose patients to bacteremia and prolonged hospitalization, some of these factors were thrombocytopenia, central venous catheter use, and profound neutropenia. Identifying these factors allows for risk stratification and optimization of antibiotic management in children with cancer and febrile neutropenia. We studied the risk factors for bacteremia in children with cancer in a pediatric hemato-oncology unit of a public third level hospital in La Paz, Bolivia. Methods A retrospective case–control study was conducted in the pediatric hemato-oncology unit at Hospital del Niño “Ovidio Aliaga Uria” in La Paz, Bolivia. The study population consisted of 115 pediatric patients (0–14 years), from which a sample of 90 children was selected: 45 with bacteremia (cases) and 45 without bacteremia (controls). Data were collected in Excel and analyzed using Epi Info 7.2.6.0 to generate tables and graphs. The odds ratio (OR) with 95% confidence intervals was calculated to identify factors associated with bacteremia. Statistical significance was set at p<0.05. Results Risk factors associated with the development of bacteremia were mainly hematologic cancer (44.0%), with acute lymphoblastic leukemia in the induction phase being the most frequent (39.6%; OR: 1.23). The use of a central venous catheter (CVC), neutropenia with an absolute neutrophil count (ANC) <500/mm3, monocytopenia, and prior antimicrobial use during previous hospitalizations showed a significant association with bacteremia (p=0.001) with OR of 28, 25, 30, and 28 respectively. In contrast, a neutropenia duration of less than 7 days was a protective factor (OR: 0.05). Regarding causative agents, most bacteremia cases were produced by Gram-negative microorganisms. Conclusion We conclude that the study highlights critical risk factors associated with bacteremia. Recognizing these factors can help physicians identify high-risk patients early. These findings underscore the importance of proactive management in pediatric oncology, prioritizing regular infection surveillance and timely interventions